QUANTITATIVE DETECTION METHOD OF ASSEMBLY TIGHTNESS OF BOLTED ROTOR BASED ON GHM MULTIWAVELET - YAN Qiang; ZHANG XiaoLi; ZHAO JunFeng; YANG Ji; SHEN YanBin (Jixie qiangdu)
The bolted rotor is a typical rotor structure with light weight, high strength, good rigidity, flexible selection of all kinds of wheel materials, etc., which is formed by pressing and combining several sections of rotors or discs and is widely used in aero-engines and gas turbines. Aiming at blind assembly, trail assembly and inconsistent assembly tightness of bolted rotor, and the degradation and loosening of bolt tightness in service, a quantitative detection method of bolt assembly quality based on GHM multiwavelet was proposed. Using the GHM multiwavelet with excellent characteristics such as symmetry, compactness, orthogonality, vanishing moment and high order vanishing moment, feature extraction of the bolted rotor assembly tightness states was performed. The quantitative detection index of assembly quality was defined by the relative energy band distribution based on multiwavelet. The experimental verification shows that the proposed method can accurately identify six kinds of bolt states from tightness to looseness.